(untitled) (Czech Journal of Multidisciplinary Innovations, 2023)
The architectural, cultural, and religious heritage is a rich record of the creativity of nations, an icon of their genius, a memory that preserves their values, a component of their ancient historical identity across the ages, and a symbol of their uniqueness among other cultures and civilizations.